The quantitative evaluation of subjective satisfaction with digital media in L2 acquisition in younger adults: A study from Europe, Asia, and Latin America - Pikhart, Marcel; Klimova, Blanka; Al-Obaydi, Liqaa Habeb; Dziuba, Szymon; Cierniak-Emerych, Anna (Frontiers in Psychology, 2022)
Foreign language learning has recently been transferred into an online or hybrid mode and this has brought many challenges for both the teachers and the students. Thus, the purpose of this study is to explore students’ subjective satisfaction with the use of digital media in their L2 acquisition conducted online, as well as to provide specific recommendations for meeting students’ needs in digital media L2 instruction. This is large-scale comparative research conducted in the Czech Republic, Poland, Romania, Iraq, and Malaysia. The data were collected through an online questionnaire in May, June, and July 2021 in the given countries. The findings reveal that students’ subjective satisfaction that is related to students’ attitudes toward the online learning process, the general usefulness of language, the role of the teacher, and the matters that affect the general process of teaching and learning all gained the positive answers. Whereas the items that are related to students’ subjective satisfaction toward language skills, digital-based reading, the effectiveness of online education over face-to-face, and communicating with teachers and peers via social media are all gained negative results. These results need further analysis but they can be an impetus for much larger research and further implications to optimize L2 acquisition.